COST AND TIME ANALYSIS USING EARNED VALUE METHOD ON THE CONSTRUCTION OF THE NATIONAL KEDIRI AIRPORT ACCESS ROAD PHASE 1 KEDIRI - NGANJUK - Pramadha, Ichsan Yanuansyah; Tjendani, Hanie Teki; Witjaksana, Budi (Transpublika Publisher, 2024)
Project completion delays have adverse consequences on a contractor's credibility and result in additional penalty costs, reducing potential profits. To mitigate these issues and optimize project outcomes, refining activity schedules and budgets is crucial. The Earned Value Method proves effective in monitoring and controlling project activities. In the case of the Kediri airport access road construction project, weeks 1 to 6 revealed a negative Cost Variance (CV), indicating higher-than-planned costs, while weeks 7 to 8 showed a positive CV, suggesting costs were lower than anticipated. Schedule Variance (SV) for the 1st week was unfavorable, indicating a delay, and SV>1 from weeks 2 to 8 signaled a project delay. The Estimate to Complete (ETC) is IDR 17,470,510,292.77, and the Estimate at Complete (EAC) is IDR 32,509,153,464.05. The Time Estimate (TE) forecasts project completion in 89 calendar days, five days beyond the contracted 84 days. Employing the Earned Value Method enhances project performance evaluation and decision-making to avoid delays and cost overruns.